Pengaruh Media Pembelajaran Berbasis TPACK terhadap Numerasi Siswa Kelas 5 SD Gugus Jangka Bireuen: The Effect of TPACK-Based Learning Media on the Numeracy Skills of 5th-Grade Students in the Jangka Bireuen Cluster - Sri Wahyuni; Rambang Muharramsyah; Syifa Saputra3 (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Indonesian students' literacy and numeracy skills remain low, including among fifth-grade students in the Jangka Cluster, Bireuen Regency. This study aimed to examine the impact of learning media based on Technological Pedagogical Content Knowledge (TPACK) on improving the literacy and numeracy skills of fifth-grade elementary school students. A quantitative approach was employed using a quasi-experimental design—specifically, a non-equivalent control group design. The sample consisted of 60 fifth-grade students: 30 students from SD Negeri 9 Jangka (experimental group) who received TPACK-based instruction over six sessions, and 30 students from SD Negeri 3 Jangka (control group) who received conventional instruction. Data were analyzed using the Shapiro–Wilk normality test, Levene's test of homogeneity of variance, the Mann–Whitney U test, and simple linear regression via IBM SPSS Statistics version 27. The Mann–Whitney test revealed significant differences between the two groups in both literacy (Sig. = 0.007; medium effect size) and numeracy (Sig. = 0.040; small-to-medium effect size), with the experimental group showing higher mean ranks in both aspects. However, regression results indicated that studenstudents'ption scores regarding the TPACK media did not significantly influence literacy or numeracy N-Gain scores (Sig. = 0.648; R² = 0.008); the discrepancy between these analyses suggests that the media's effectiveness operates at the group (aggregate) level rather than serving as a linear predictor at the individual level. TPACK-based learning media positively contributed to improving student literacy and numeracy at the group level, even though individual student perceptions of the media did not directly predict the magnitude of these skill improvements.